2014
DOI: 10.1186/s13071-014-0541-3
|View full text |Cite
|
Sign up to set email alerts
|

The metazoan parasite communities of the shoal flounder (Syacium gunteri) as bioindicators of chemical contamination in the southern Gulf of Mexico

Abstract: BackgroundBecause agriculture and offshore oil extraction are significant economic activities in the southern Gulf of Mexico, high concentrations of nutrients and hydrocarbons are expected. As parasite communities are sensitive to environmental impacts, these contaminants should have an effect on metrics such as species richness, relative abundance and similarity. Consequently, these community metrics can be used as indicators of aquatic environmental health. Our objectives were to describe the parasite commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…The unexpected combined effect of alkalinity and pH upon the parasites is very suggestive, and we speculate that the potential interaction between pH and the decrease in the number of parasites cannot be disregarded. The community metrics chosen generally had robust statistically significant associations with both physicochemical and contaminant variables, which supports the ecological relevance of these parameters as indicators of aquatic environmental health [5,71].…”
Section: Discussionmentioning
confidence: 54%
“…The unexpected combined effect of alkalinity and pH upon the parasites is very suggestive, and we speculate that the potential interaction between pH and the decrease in the number of parasites cannot be disregarded. The community metrics chosen generally had robust statistically significant associations with both physicochemical and contaminant variables, which supports the ecological relevance of these parameters as indicators of aquatic environmental health [5,71].…”
Section: Discussionmentioning
confidence: 54%
“…Samples were obtained from March 2015 to June 2021. Oceanographic sampling procedures for the collection of fishes have been described elsewhere (i.e., Vidal-Martínez et al 2014, 2019; García-Teh et al 2022). Host dissection procedures followed Vidal-Martínez et al (2014, 2019) and García-Teh et al (2022).…”
Section: Methodsmentioning
confidence: 99%
“…have been reported from Micropogonias undulatus (Linnaeus, 1766) from Laguna Madre, Tamaulipas, Mexico (Iruegas-Buentello 1999). Particularly, recent studies of helminth communities from intestines of three flatfish species (Paralichthyidae) (i.e., Cyclopsetta chittendeni Bean, 1895; Syacium gunteri Ginsburg, 1933; and Syacium papillosum (Linnaeus, 1758)) from oceanic sites in the southern Gulf of Mexico (s-GoM) have reported S. sagittifer as the most prevalent adult acanthocephalan parasite species (Vidal-Martínez et al 2014, 2019; Centeno-Chalé et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…All the parasites found of different taxa were counted in situ and divided into two groups. The first group, which included all the parasites (i.e., digeneans, nematodes, and acanthocephalans) except O. wageneri, was preserved in 70% alcohol and used for both molecular and morphological taxonomy (see Vidal-Martínez et al (2014) for details). In contrast, the second group, which included the O. wageneri larvae, was frozen at −20°C immediately after extraction from the fish without any solution.…”
Section: Collection and Examination Of Fishmentioning
confidence: 99%
“…Oncomegas wageneri is a larval cestode infecting flatfishes collected from oil extraction zones of the Mexican Gulf of Mexico (Vidal-Martínez et al 2014;Centeno-Chalé et al 2015;Vidal-Martínez et al 2015;Martínez-Aquino et al 2019). This parasite is a good candidate for the detection of PAH metabolites because it has a wide geographical distribution in the Gulf of Mexico, has a high prevalence and mean abundance in its host, and inhabits the intestine of the flatfishes where it can be exposed to whatever the host is ingesting (including food contaminated with PAH) (Vidal-Martínez et al 2014). Support for this suggestion comes from the findings of Oluoch-Otiego et al (2016), who have shown that intestinal cestodes bioaccumulate higher levels of polychlorinated biphenyls (PCBs) than their hosts.…”
Section: Introductionmentioning
confidence: 99%